2012
DOI: 10.1093/cercor/bhs045
|View full text |Cite
|
Sign up to set email alerts
|

Different Timescales for the Neural Coding of Consonant and Vowel Sounds

Abstract: Psychophysical, clinical, and imaging evidence suggests that consonant and vowel sounds have distinct neural representations. This study tests the hypothesis that consonant and vowel sounds are represented on different timescales within the same population of neurons by comparing behavioral discrimination with neural discrimination based on activity recorded in rat inferior colliculus and primary auditory cortex. Performance on 9 vowel discrimination tasks was highly correlated with neural discrimination based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
121
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(134 citation statements)
references
References 93 publications
12
121
0
Order By: Relevance
“…While the activation patterns were complex for both stimuli, they were sparsely overlapping and the local patterns were distributed across many regions of the auditory cortex. Perez et al (2013) found that different coding strategies were used for vowels and consonants. They found vowel discrimination corresponded largely to neural spike counts in certain brain regions, while consonant discrimination correlated to neural spike timing and not to counts if timing information was eliminated.…”
Section: Ockham's Razor and Levels Of Analysismentioning
confidence: 99%
“…While the activation patterns were complex for both stimuli, they were sparsely overlapping and the local patterns were distributed across many regions of the auditory cortex. Perez et al (2013) found that different coding strategies were used for vowels and consonants. They found vowel discrimination corresponded largely to neural spike counts in certain brain regions, while consonant discrimination correlated to neural spike timing and not to counts if timing information was eliminated.…”
Section: Ockham's Razor and Levels Of Analysismentioning
confidence: 99%
“…where rats were trained to discriminate consonants and vowels) and neural recording in the IC and in the auditory cortex, studies have shown that that the brain represents different sounds (e.g. consonants and vowels) at different points in time (Perez et al, 2013). The time lapse between responses in the IC and in the auditory cortex supports the notion that consonant and vowel sounds are represented by neural activity patterns occurring on different timescales (Poeppel, 2003;Carreiras and Price, 2008), and suggests that voice processing operates through the gradual transformation from low-level acoustic information to high-level cognitive category.…”
Section: Inferior Colliculusmentioning
confidence: 99%
“…A peristimulus time histogram (PSTH) classifier (Foffani and Moxon 2004;Engineer et al 2008;Perez et al 2012) was used to calculate the neural discrimination between speech stimuli in units of percent correct. The classifier randomly picked five sites (each having 20 sweeps) at a time and made a template from 19 sweeps (the sweep being considered was excluded) for each speech sound.…”
Section: Neural Recordings and Neural Data Analysismentioning
confidence: 99%